The income approach to measuring poverty: A note on human welfare below the line - Kumar, Shubh K. (International Food Policy Research Institute, 1985)
Measurements of the prevalence of poverty often provide a starting point ofr analyzing the welfare implications of policies and programs. The work of Dharm Narain provides a further example of the potential of these measurement to illuminate the development processes that contribute to human well-being.